The Ability of Iraqi Students in Using English Prepositions - Jaafar Isa Abdulabbas (Genius Journals, 2022)
Learning English prepositions is not as easy as other parts of speech. Since prepositions are function words, they may form different functions and have different meanings, depending on the context in which they are used. This literal translation cannot be considered. Alongside their importance in writing, prepositions form one of the most difficult parts suffered by the majority of Iraqi students. In our universities, they are tough only the structure of prepositions. Thus, the present study focuses on the difficulties faced by Iraqi students, especially 4th-grade at the University of Babylon/ English Department
Keywords: English prepositions; Iraqi students; difficulties; different